If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12r-3(r+5)=4(3r-6)-3
We move all terms to the left:
12r-3(r+5)-(4(3r-6)-3)=0
We multiply parentheses
12r-3r-(4(3r-6)-3)-15=0
We calculate terms in parentheses: -(4(3r-6)-3), so:We add all the numbers together, and all the variables
4(3r-6)-3
We multiply parentheses
12r-24-3
We add all the numbers together, and all the variables
12r-27
Back to the equation:
-(12r-27)
9r-(12r-27)-15=0
We get rid of parentheses
9r-12r+27-15=0
We add all the numbers together, and all the variables
-3r+12=0
We move all terms containing r to the left, all other terms to the right
-3r=-12
r=-12/-3
r=+4
| 4+4+4x=4x | | 2/5(10x-15)=13 | | r/14-1=0 | | (384+2x)/7=80 | | 2/x=140 | | 5u-14=3(u+6)-2 | | 7b=-9-2b | | 6+5y=-7 | | P=5q-7 | | 16x+2=42x+4 | | 25000-12.5x=0 | | -9(t-12)=4(t-15) | | 5u-13=3(u+6)-2 | | -7(6k-8)+8k=192 | | -3v+6v=5v | | 22x+3=-3+23x | | 7(3z-2)=28 | | 15x+25=10X-30+415 | | 9t+2=7t+14 | | |z|+2=–2 | | -10(x-3)=3.2 | | n/7+9=11 | | 5-3y=-2y+5 | | 5/2x+8=3 | | 9/2+1/9t=9 | | 40=16–8r | | 22+m=30 | | 3x+3x-5x=31 | | 45+25x=810 | | 7(x-3)+5x=3(x+5) | | -(6x+7+8=19 | | 2x+5+4x-1=5x+37 |